2017
DOI: 10.1186/s12890-017-0558-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of alarmin HNPs 1–3 associate with lung dysfunction after cardiac surgery in children

Abstract: BackgroundEarly onset of lung injury is considerable common after cardiac surgery and is associated with increasing in morbidity and mortality, but current clinical predictors for the occurrence of this complication always have limited positive warning value. This study aimed to evaluate whether elevated plasma levels of human neutrophil peptides (HNPs) 1–3 herald impaired lung function in infants and young children after cardiac surgery necessitating cardiopulmonary bypass (CPB).MethodsConsecutive children yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Considering that CIRP participates in the dysfunction of endothelial cells via activation of the NLRP3 inflammasome [21], we speculated that CIRP is correlated with lung injury induced by cardiovascular surgery with CPB. As expected, after adjusting other factors, multiple linear regression analysis indicated that CIRP levels were independently associated with PaO 2 /FiO 2 and reflect the severity of lung injury [28]. These findings strengthen the conclusion that CIRP is a predictor for lung injury after cardiovascular surgery with CPB.…”
Section: Discussionsupporting
confidence: 74%
“…Considering that CIRP participates in the dysfunction of endothelial cells via activation of the NLRP3 inflammasome [21], we speculated that CIRP is correlated with lung injury induced by cardiovascular surgery with CPB. As expected, after adjusting other factors, multiple linear regression analysis indicated that CIRP levels were independently associated with PaO 2 /FiO 2 and reflect the severity of lung injury [28]. These findings strengthen the conclusion that CIRP is a predictor for lung injury after cardiovascular surgery with CPB.…”
Section: Discussionsupporting
confidence: 74%
“…However, HNP 1–3 was elevated in infants diagnosed with another inflammation-mediated disease, BPD, comparable to serum concentrations of several cytokines ( 27 ). Interestingly, previous studies found an elevation of serum HNP in children with poor pulmonary outcome ( 15 ), assuming its function as an alarmin may be of use as a prognostic marker of the inflammation mediating the lung disease. This aspect needs to be confirmed in prospective trials in order to evaluate whether HNP adds information within the multifactorial risk profile for BPD.…”
Section: Discussionmentioning
confidence: 99%
“…In preterm infants, infection and inflammation may influence systemic levels of APPs ( 6 , 7 , 13 15 ). In line with that, LF has been proposed to have a beneficial effect by counter-regulating systemic inflammation in neonatal sepsis ( 16 ), which was not confirmed by other investigators ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…If severe cases evolve into acute respiratory distress syndrome (ARDS), the mortality rate is close to 30% (4,5). According to clinical experience, the earlier lung damage is detected, the more successful the treatment will be (6)(7)(8). Therefore, in-depth study of the mechanism of CPB-related lung injury, discovery, and validation of certain alarming biomarker of CPB-related lung injury in cardiac surgery patients will greatly contribute to early diagnosis and effective treatment decisions making.…”
Section: Introductionmentioning
confidence: 99%